An experimental study on the effect of nanoparticles with novel tamarind seed methyl ester for diesel engine applications. (15th May 2018) - Dhana Raju, V.; Kishore, P.S.; Nanthagopal, K.; B.Ashok,
Graphical abstract: Highlights: Biodiesel is synthesized from tamarind seed for diesel engine applications. Increase in brake thermal efficiency for alumina oxide addition with blended fuel. Nanoparticle addition with blend fuel is shown significant reduction in emissions. Smoke opacity is considerably lower for nanoparticle addition with biodiesel blend. Addition of nanoparticle with tamarind biodiesel blend increases the peak pressure. Abstract: The present experimental research work is focused on enhancing the performance, combustion and emission characteristics of a novel tamarind seed methyl ester using nanopartcles. Initially, the tamarind seed methyl ester is blended with diesel at 10%, 20% and 30% concentrations by volume and all the fuel samples have been tested in diesel engine for the selection of an optimum blend for nanoparticle addition. Then two nano additives namely alumina oxide and multi-walled carbon nano tubes are doped with an optimum tamarind seed methyl ester blend at concentrations of 30 ppm and 60 ppm for a comparative analysis. The study revealed that the addition of 60 ppm of alumina oxide with tamarind seed methyl ester blend has shown 1.6% higher brake thermal efficiency than that of tamarind seed methyl ester blend. The reformulation of tamarind seed methyl ester blend by nanoparticle addition has shown 15–51% and 24–68% reduction in carbon monoxide and unburned hydrocarbon emissions respectively. Further, oxides of nitrogen emission are reduced by 7–9% during nanoparticle addition with tamarind seed methyl ester blend. On the other hand, the nanoparticle addition with tamarind seed methyl ester blend is produced better combustion characteristics compared to tamarind seed methyl ester-diesel blend. Therefore, the present study showed that the diesel engine characteristics for tamarind seed methyl ester blend operation could be improved with dispersion of nanoparticle.